2020
DOI: 10.3390/s20020517
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and Terrestrial Observations of the Thermal Environment of Urban Areas Surrounding a High-Rise Building during the Japanese Winter

Abstract: We investigated the distribution of air temperature (Ta) and the factors affecting it in low-rise areas surrounding an isolated high-rise building during the Japanese winter. The study site was the central part of a regional city in Japan (36°5′ N, 140°12′ E), lying north-east of the Tokyo metropolitan area. The daytime surface temperature (Ts) in the shade is generally considered to be comparable to Ta; however, according to airborne remote sensing conducted in December 2009 where a multi-spectral scanner was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The research on architectural design from the perspective of low carbon is of great significance to the control of global greenhouse effect [21][22][23][24][25]. Oshio et al [26] relates to the low carbonization of large space buildings in areas hot in summer and cold in winter, puts forward matters needing attention in the rational utilization of natural lighting and natural ventilation and the rational selection of building materials, and studies the selection of natural ventilation channels and enclosure materials from the above two perspectives. Hu et al [27] optimizes the comprehensive evaluation indexes of low-carbon buildings, realizes the analysis and calculation of carbon emission index, analyzes the influencing factors hindering the development of low-carbon buildings, and gives the evaluation method of lowcarbon building structure.…”
Section: Introductionmentioning
confidence: 99%
“…The research on architectural design from the perspective of low carbon is of great significance to the control of global greenhouse effect [21][22][23][24][25]. Oshio et al [26] relates to the low carbonization of large space buildings in areas hot in summer and cold in winter, puts forward matters needing attention in the rational utilization of natural lighting and natural ventilation and the rational selection of building materials, and studies the selection of natural ventilation channels and enclosure materials from the above two perspectives. Hu et al [27] optimizes the comprehensive evaluation indexes of low-carbon buildings, realizes the analysis and calculation of carbon emission index, analyzes the influencing factors hindering the development of low-carbon buildings, and gives the evaluation method of lowcarbon building structure.…”
Section: Introductionmentioning
confidence: 99%
“…In these spaces, even if they are relatively small, the presence of a sensible heat source/sink can cause large air temperature differences. For example, in urban spaces, in shaded areas of high-rise buildings [3] and street canyons [4], low-temperature ground surfaces and building walls act as heat sinks during the day, and a reduction in air temperature of more than 2°C has been confirmed in some cases. In buildings, depending on the location of the air conditioning vents, a large air temperature distribution is generated in the room (e.g., Huang et al [5] reported a temperature irregularity of approximately 2.4°C), which affects the comfort of the occupants.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the time constant of measurement is not very sensitive because of the sensor heat capacity [10]. Meanwhile, mobile observations are sometimes carried out to obtain the spatial distributions of the air temperature in urban sites [3,11,12]. However, temporal variations in the meteorological conditions (e.g., dominant wind, solar radiation, and air temperature) during the observations make it difficult to comprehensively understand the spatial variations.…”
Section: Introductionmentioning
confidence: 99%